Fabrication and characterization of nanodelivery platform based on Chitosan to improve the anticancer outcome of sorafenib in Hepatocellular Carcinoma - Albalawi, Fahad; Hussein, Mohd Zobir; Fakurazi, Sharida; Masarudin, Mas Jaffri (Nature Research, 2023)
Chitosan nanoparticles (CS NPs) showed promising results in drug, vaccine and gene delivery for the treatment of various diseases. The considerable attention towards CS was owning to its outstanding biological properties, however, the main challenge in the application of CS NPs was faced during their size-controlled synthesis. Herein, ionic gelation reaction between CS and sodium tripolyphosphate (TPP), a widely used and safe CS cross-linker for biomedical application, was exploited. The development of nanodelivery platform, namely Sorafenib-loaded chitosan nanoparticles (SF–CS NPs), was constructed in order to improve SF drug delivery to human Hepatocellular Carcinoma (HepG2) cell lines. The NPs were artificially fabricated using an ionic gelation technique. A number of CS NPs that had been loaded with an SF were prepared using different concentrations of sodium tripolyphosphate (TPP). These concentrations were 2.5, 5, 10, and 20 mg/mL, and they are abbreviated as SF–CS NPs 2.5, SF–CS NPs 5.0, SF–CS NPs 10, and SF–CS NPs 20 respectively. DLS, FTIR, XRD, HRTEM, TGA, and FESEM with EDX and TEM were used for the physiochemical characterisation of SF–CS NPs. Both DLS and HRTEM techniques demonstrated that smaller particles were produced when the TPP content was raised. In a PBS solution with a pH of 4.5, the SF exhibited efficient release from the nanoparticles, demonstrating that the delivery mechanism is effective for tumour cells. The cytotoxicity investigation showed that their anticancer effect against HepG2 cell lines was significantly superior than that of free SF. In addition, the nanodrug demonstrated an absence of any detectable toxicity to normal adult human dermal fibroblast (HDFa) cell lines. This is a step towards developing a more effective anticancer medication delivery system with sustained-release characteristics, which will ultimately improve the way cancer is managed.